STATE POLICY IN PEDIATRIC HEALTH CARE - A SCIENTIFIC APPROACH - Yu.E. Lapin ("Paediatrician" Publishers LLC, 2006)
The article highlights the importance of scientific approach in development of state policy in pediatrics healthcare as an integral part of policy guarding the benefits of children in current socio economic conditions in Russia. The author gives definition to the terms as «child's health» and «state policy in pediatric healthcare» and proves the methodology and practice of the current social policy in solving problems of children to be untenable. The author suggests to revise our perception of children - from the «social groups» to a «growth zone of society». Key words: child health, child rights, state policy, legislative back ground.